KEPUASAN DAN RETENSI GURU TERHADAP SISTEM PELATIHAN JARAK JAUH BALAI DIKLAT KEAGAMAAN INDONESIA - Muhammad Alfarizi; Ngatindriatun Ngatindriatun (Balai Diklat Keagamaan Jakarta, 2023)
Abstract Digital transformation after the COVID-19 Pandemic has touched the education sector through the development of e-learning. The use of e-learning media is not only for formal education learning but has also begun to feel the HR training department or directorate at state institutions. All ministries and state agencies in Indonesia must organize online education and training by utilizing e-learning. The BDK of the Ministry of Religion in Indonesia is very active in organizing distance education, especially for madrasa teachers, through the independent development e-learning platform for each BDK of the Ministry of Religion. This study is intended to investigate the factors driving satisfaction and retention of MoRA BDK distance training participants using e-learning. The study was carried out quantitatively based on a survey. It involved 206 madrasah teacher respondents who had attended the Ministry of Religion's BDK distance training or distance courses drawn by convenience sampling. This study found that cognitive uptake and social presence influence the perceived usefulness and ease of use of e-learning. In addition, this study determines that perceptions of the usefulness and ease of use of e-learning significantly influence satisfaction and, ultimately, electronic retention of MoRA BDK e-learning. This study recommends increasing system capability by combining utility and intrinsic features and developing a collaborative assignment system. The instructor's presence must be strengthened via live chat or video conference scheduling. The Ministry of Religion of the Republic of Indonesia needs to formulate a more detailed distance training policy, including appropriate training standards, to achieve the expected competencies of participants. Abstrak Transformasi digital pasca Pandemi COVID-19 menyentuh hingga sektor pendidikan melalui pengembangan e-learning. Pemanfaatan media e-learning tidak hanya untuk pembelajaran pendidikan formal, namun juga mulai menyentuh bagian atau direktorat pelatihan SDM pada lembaga negara. Saat ini seluruh kementerian dan lembaga negara di Indonesia dituntut menyelenggarakan pendidikan dan pelatihan secara online dengan memanfaatkan e-learning. BDK Kemenag di Indonesia sangat aktif menyelenggarakan pendidikan jarak jauh khususnya bagi guru madrasah melalui platform e-learning pengembangan mandiri masing-masing BDK Kemenag. Studi ini ditujukan untuk menginvestigasi faktor yang mendorong kepuasan dan retensi peserta pelatihan jarak jauh BDK Kemenag dalam menggunakan e-learning. Studi dilaksanakan secara kuantitatif berbasis survei dan melibatkan 206 responden guru madrasah yang pernah mengikuti pelatihan atau kursus jarak jauh BDK Kemenag yang ditarik dengan convenience sampling. Studi ini menemukan bahwa penyerapan kognitif dan kehadiran sosial memiliki pengaruh terhadap persepsi kegunaan dan kemudahan penggunaan e-learning. Selain itu studi ini menetapkan persepsi kegunaan dan kemudahan penggunaan e-learning secara signifikan mempengaruhi kepuasan dan pada ujungnya retensi elektronik kepada e-learning BDK Kemenag. Studi ini merekomendasikan peningkatakan kapabilitas sistem melalui penggabungan fitur utilitas dan intrinsik disertai pengembangan sistem kolaboratif penugasan. Kehadiran instruktur perlu diperkuat baik melalui fitur live chat ataupun penjadwalan video conference. Kementerian Agama RI perlu merumuskan kebijakan pelatihan jarak jauh yang lebih detail termasuk standar pelatihan yang sesuai agar kompetensi yang diharapkan pada peserta tercapai.